TINJAUAN HUKUM PIDANA ATAS SISTEM PERADILAN PIDANA DALAM MELINDUNGI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DI LINGKUNGAN PONDOK PESANTREN - Maghfirah Ayuni; H Benny Irawan; Muhyi Mohas (Journal of Innovation Research and Knowledge, 2025)
The crime of sexual violence is a serious crime (felony) that often occurs in educational institutions, but the implementation of the law on sexual violence is also hampered because not all law enforcement officers understand this law as the criminal justice system is not run properly, and provides a severe dilemma for law enforcement in providing appropriate decisions according to facts and legal review. Identification of problems in this study is 1) How the criminal justice system in protecting victims in the settlement of cases of sexual violence as associated with law No.12 of 2022; and 2) how the consideration of judges in deciding cases of sexual violence in the boarding school environment; research methods using normative legal research with a case approach. This study found that the criminal justice system is not run properly according to the Sexual Violence Crime Act and the consideration of judges who are less precise in determining the article, the punishment is too light and less fair for victims. This study concludes that 1) the criminal justice system is closely related to the criminal legislation, but even if the law fully regulates it, that the criminal justice system, namely the integrated criminal justice system from the investigator to the implementation of the decision, that cases of sexual violence in the process of trial must be carried out behind closed doors, If in the bercara process that has been regulated by the KUHAP that the hearing in the asusila case is closed and also other special regulations such as Law No. 12 of 2022 on sexual violence crimes, especially in Article 59 paragraph 2, that in mentioning the victim's identity should not be mentioned where it is not carried out properly this can result in a violation of the article and can cancel the decision. That in terms of protecting victims, the criminal justice system is due process of model as the principle of the criminal justice system Due Process Model to protect the community in this case protects victims related to human rights. 2) consideration of the judge in deciding the case of sexual violence as the case of sexual violence in the boarding school, with consideration of the judge stating that it is true that the defendant inserted his genitals into the genitals of the victim's witness, the judge in applying the article there is a mistake that is the indictment charged by the Public Prosecutor with alternative charges against the defendant, so the judge decided the defendant had been found guilty of violating Article 289 of the Criminal Code regarding molestation. In addition, the judge was mistaken in considering the legal facts that showed that the defendant was actually guilty of committing the Act stipulated in Article 285 of the Criminal Code regarding rape, in addition to the application of the article that was not in accordance with the panel of judges decided with criminal sanctions for 7 years. In the theory of Justice which means that justice is a legal goal to be achieved, but the purpose of law is not only justice but also for legal certainty and expediency.